INFLUENCE OF LEARNING COMMUNITIES THROUGH DEEP LEARNING STRATEGIES TO IMPROVE TEACHER COMPETENCE AND PERFORMANCE - Purwanti; Gunawan Gunawan (SOSIOEDUKASI, 2026)
This study aims to examine the influence of learning community activities with a deep learning approach on improving teacher competence and performance as well as the correlation between competence and teacher performance. The study used a quantitative method with an experimental design involving the experimental group and the control group. Data collection techniques include questionnaires, documentation, and observations. Data analysis included statistical tests of normality, homogeneity, t-test, and Pearson correlation test. The results of the prerequisite test showed that the data had a normal distribution and were homogeneous, making them eligible for parametric analysis. The results of the independent sample t-test showed a significance value of 0.001 (< 0.05) with a mean difference of 10.083, which indicates a significant difference between the two groups, where the experimental group obtained a higher score than the control group. In addition, the Pearson correlation test produced a significance value of 0.002 with a correlation coefficient of 0.781 which is included in the strong and positive categories, thus showing a close relationship between competence and teacher performance. These results reinforce that the implementation of deep learning-based learning communities is able to improve competence while having an impact on significantly improving teacher performance.